An Analysis of the Applicability of the CAPM Model on the Croatian Capital Market - Marijanović Bilić, Maja; Beljo, Ivana; Devčić, Kristina (Oeconomica Jadertina, 2017)
Successful investment management implies the valuation of financial assets as well as the assessment of the risk of investing in financial assets. The aim of each investor is to invest in financial assets that will bring him as much yield as possible with minimum risk. It is precisely this relationship between yield and risk that many researchers are interested in. The aim of this paper is to analyse the applicability of the CAPM model on the financial market of the Republic of Croatia, to examine the adequacy of the beta coefficient as a market risk measure and to analyse whether CROBEX could be considered as a good substitute for the market portfolio. Given that the risk of investing in financial assets depends on numerous macroeconomic variables, it can be measured as the sensitivity of the return on investment in financial assets relative to the yield of the overall market portfolio. The beta coefficient was used as a risk measure. A correlation and regression analysis showed that there is no significant linear relationship between the beta coefficient and the expected yields, or more precisely, that the beta coefficient is not an adequate measure of risk on the Croatian capital market. In addition, it has been shown that the official stock market index of the Croatian capital market (CROBEX) cannot serve as an acceptable substitute for the market portfolio as it does not lie on an efficient border.